Design and fabrication of smoke piping system - Ahmad Ikmal 'Akif, Abdul Khalil (2013)
This report shows the design and fabrication of smoke piping system.The problem from the instrument is the smoke flow is late to fill the air smoke rig. It fills the rig with natural pressure come from smoke generator. It takes a long time to fill it.The objective of the report are to make the smoke go more faster to air flow bench and to control volume enter the air flow bench using toggle switch.Design generation is showed and solid three dimensional structures modeling of the smoke piping system was developed with SolidWorks software. The result from testing the smoke piping system shows that the system able to suck smoke in short duration. Ideas for improvement for the smoke piping system also provided to further improve the smoke piping system.